2020
DOI: 10.1021/acsnano.9b08494
|View full text |Cite
|
Sign up to set email alerts
|

A General Strategy to Atomically Dispersed Precious Metal Catalysts for Unravelling Their Catalytic Trends for Oxygen Reduction Reaction

Abstract: Atomically dispersed precious metal catalysts have emerged as a frontier in catalysis. However, a robust, generic synthetic strategy toward atomically dispersed catalysts is still lacking, which has limited systematic studies revealing their general catalytic trends distinct from those of conventional nanoparticle (NP)-based catalysts. Herein, we report a general synthetic strategy toward atomically dispersed precious metal catalysts, which consists of "trapping" precious metal precursors on a heteroatom-doped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 73 publications
0
90
0
1
Order By: Relevance
“…This process requires large-scale production equipment, and further transportation requires handling of large amounts of unstable and hazardous solutions 5 . Thus, the usage of an electrochemical oxygen reduction reaction (ORR) through a 2-electron pathway to produce H 2 O 2 is a highly desirable method that can be safe, on-site, portable, and green 6 21 . However, this method critically requires the development and screening of low-cost and high-performance electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…This process requires large-scale production equipment, and further transportation requires handling of large amounts of unstable and hazardous solutions 5 . Thus, the usage of an electrochemical oxygen reduction reaction (ORR) through a 2-electron pathway to produce H 2 O 2 is a highly desirable method that can be safe, on-site, portable, and green 6 21 . However, this method critically requires the development and screening of low-cost and high-performance electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting Pt SACs showed a high activity (3.10 A mg À 1 Pt ) and selectivity (~95 %) towards H 2 O 2 production in 0.1M KOH. In another study, Kim et al [59] developed a general route based on SiO 2 coating to synthesize SACs of various noble metals (i. e., Os, Ru, Rh, Ir and Pt) supported on carbon nanotubes (CNTs) (Figure 2a-c). They first coated CNT with an ionic liquid (IL) containing the metal precursors and annealed the sample at 450°C.…”
Section: Noble Metal Sacsmentioning
confidence: 99%
“…Recently, Pt SACs have received much attention as a way to dramatically reduce Pt use in PEMFCs . The ORR follows either a two‐electron pathway (O 2 (g)+2H + (aq)+2e − →H 2 O 2 (aq), E° =+0.690 V) or a four‐electron pathway (O 2 (g)+4H + (aq)+4e − →2H 2 O (l), E° =+1.229 V) . Most Pt SACs reported so far have followed the two‐electron pathway, producing H 2 O 2 .…”
Section: Figurementioning
confidence: 99%
“…Highly oxidic Pt single‐atoms formed on N‐doped carbon support do not show high activity for ORR, following the two‐electron pathway. Many other works have also confirmed that Pt single‐atoms on doped carbon supports followed the two‐electron pathway, while the corresponding Pt nanoparticles followed the four‐electron pathway . However, we do not intend to insist that ORR will not follow the four‐electron pathway for all Pt single‐atoms.…”
Section: Figurementioning
confidence: 99%